Pengembangan Media Pembelajaran Canva Berbasis Warna untuk Meningkatkan Hafalan dalam Pembelajaran Bahasa Indonesia Pada Siswa Kelas II SD - Uswatun Hasanah; Sumadi; Ina Agustin (PEDAGOGIC: Indonesian Journal of Science Education and Technology, 2026)
This study aims to develop and test the feasibility, practicality, and effectiveness of color-based Canva learning media in improving students' memorization skills in Indonesian language subjects for grade II of Elementary School. The research method used is Research and Development (R&D) with the ADDIE model which includes five stages, namely analysis, design, development, implementation, and evaluation. The product developed is a Canva-based teaching media with the planned use of color elements to support students' memory in active and passive sentences. This research was conducted at the UPT SDN Panyuran 2 with research subjects consisting of one media expert, one material expert, and grade II students. Data collection techniques used validation questionnaires from media experts and material experts, teacher response questionnaires, as well as observation sheets and student learning outcome tests. The results showed that the developed media obtained a very feasible level of feasibility with a validation percentage of media experts of 88% and material experts of 85%. The practicality test based on teacher responses showed a percentage of 87.55% with a very practical category. The effectiveness test demonstrated improved learning outcomes, marked by an average pretest score of 72 and a posttest score of 89, along with an N-Gain score of 0.74, in the high category. Thus, the color-based Canva learning tool was deemed feasible, practical, and effective for improving memorization in second-grade elementary school students.